A critical analysis of the networking experiences of female entrepreneurs: a study based on the small business tourism sector in Sri Lanka - H. A. K. N. S. Surangi (Journal of Innovation and Entrepreneurship, 2022)
Abstract This study expands on current knowledge through how female entrepreneurs form and develop their networks in the Sri Lankan context. It adopts social constructionism philosophy and narrative design to explore the female entrepreneurs' networking behaviour. Thematic analysis is used to understand the life stories of fourteen women entrepreneurs in the tourism sector. Findings suggest that female entrepreneurs are likely to rely on more informal recruitment methods and informal training practices. They have strong relationships with local communities, but they focus on customers beyond the locals. Seasonality within tourism has emphasised tourism literature due to its disruptive effect on economic transactions. However, less of the literature has examined the social effects of seasonality, which is where this study can contribute by exploring how gender roles related to social and domestic responsibilities are renegotiated during the low and high seasons when tourism entrepreneurs re-adjust to new time-demand realities. Nevertheless, the narrative research design is not widely used in the Sri Lankan context. Therefore, this article adds to the entrepreneurial networking knowledge by analysing stories about female entrepreneurs' experiences and social constructionist perspectives.